Narration in Health Communication for Stunting - Scwarskof Turnip (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: Globally, about 1 of 4 children under 5 years old was stunted. An estimated 80% of 165 million stunted children live in 14 countries. Stunting and other forms of under nutrition reduce a child chance of survival, while also hindering optimal health and growth. Health communication is a key task in the worldwide to prevent the risk of stunting.This study aimed to describe the health communication for stunting prevention.Subjects and Method: This was a qualitative case study. The theme of this study was health communication for stunting prevention. The data were collected by in-depth interview, observation, and document review. The data were analyzed using the notion of Narrative Theory and Health about theoretical thinking which explained the function of health narrative.Results: A number of informative and persuasive efforts through the communication approach had been carried out by the Ministry of Health to reduce the number of people suffering from stunting. A number of communication and information media were used to convey information or persuasive messages related to stunting. Those media could help the public to understanding stunting and how to prevent or overcome it.Conclusion: Health communication is important to help the public understand on how to prevent and overcome stunting.Keywords: stunting, narrative theory and health, health communicationCorrespondence: Scwarskof Turnip. Masters Program in Communication Sciences, Faculty of Social and Political Sciences, Universitas Diponegoro. Email: Scwarskoft@gmail.com.Journal of Health Promotion and Behavior (2018), 3(4): 248-256https://doi.org/10.26911/thejhpb.2018.03.04.04